Malagasyprinus, a new genus of the Saprininae from Madagascar with description of two new species (Coleoptera, Histeridae, Saprininae) (First contribution to the knowledge of the Histeridae of Madagascar) - Lackner, Tomáš (Pensoft Publishers, 2013)
Abstract. Based on the results of recent phylogenetic analysis of the higher taxa of the Saprininae as well as external morphological characters, especially the presence of deep and large prosternal foveae, and the shape and position of the sensory organs of the antennal club, the species Saprinus (s.str.) caeruleatus Lewis, 1905 is excluded from the genus Saprinus and a new genus Malagasyprinus, exclusive to Madagascar, is established for it. The new genus shows mainly characters that are apomorphic for the subfamily and contains another two, highly similar allopatric species Malagasyprinus perrieri sp. n., and Malagasyprinus diana sp. n., described herein. The three species are best separated from each other by the structure of the prosternum and male terminalia, especially the shape of the aedeagus. We re-describe Malagasyprinus caeruleatus comb. n. and provide Malagasyprinus perrieri and Malagasyprinus diana with brief differential diagnoses. All taxon descriptions are accompanied with color habitat photographs, SEM micrographs and drawings of their male genitalia. A key to the species of Malagasyprinus is given. Sensory structures of the antenna of Malagasyprinus caeruleatus comb. n. are likewise depicted herein. The systematic position of the newly erected genus is discussed. A lectotype of Saprinus caeruleatus Lewis, 1905 is designated.